If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 6x + -2 Reorder the terms: 5y = -2 + 6x Solving 5y = -2 + 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = -0.4 + 1.2x Simplifying y = -0.4 + 1.2x
| 9(4y-7)= | | -15+8-(-7)-4= | | 7x^2+5x=x^2-13 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4+(x*0.4)*0.4*0.4*0.4*0.4*0.4*0.4 | | 7(9x-15)=27 | | 5-10-3x^2=0 | | 7m+35=7m+7(m-2) | | 2-5m=17 | | .12-6x=.48 | | x-7y=48 | | 100=(x*0.4)+(x*0.4)*0.4+(x*0.4)*0.4*0.4+(x*0.4)*0.4*0.4*0.4 | | 21-3a=6-a | | 35x+40x-12=140 | | 3=3x+-36 | | f(x)=4-9x+3x | | 2x+(2x-2)+(2x-4)=180 | | 6+3*(12+x)=54 | | 11=4x | | 8-2x=25 | | (x+4)*(x^2-4)=0 | | x+(x+3)=20 | | 5c-7+16c+39= | | 4x(a+3)=12+4a | | 7(x+2)+5=5x+9 | | 12x-(4x-5)=61 | | 7(x-2)+5=5x+9 | | 5x-6x=10x | | 2+7e^4x=22 | | 3x-4y=x+2y | | -24+15x+9p-4x-4p-4= | | 3x-13=3x-2 | | X^3+6x^2+12x=8 |